You are not a gadget : A manifest - Jaron Lanier (Penguin, 2011)
Reveals how the internet is deadening personal interaction, stifling genuine inventiveness and even changing us as people. Showing us the way to a future where individuals mean more than machines, this book is a searing manifesto against mass mediocrity, a creative call to arms - and an impassioned defence of the human.